On the Old Icelandic Riddle Collection Heiðreksgátur - Vijūnas, Aurelijus (Scandinavistica Vilnensis, 2014)
In this article, the language of the Old Icelandic riddle collection Heiðreksgátur is studied, paying attention to its tropes (kennings and heiti), humour, and narration techniques. In addition to this, also literary links with other poems of the Poetic Edda are discussed.